Perceptions and manifestations of discrimination, violence and exclusion at the Popular University of Cesar (UPC): A Descriptive Analysis - Jiménez, Kellys Del Carmen Jiménez; Abril, Jorge Antonio Jurado; Vidal, Sixta Dalia Duran; Tafur, Ender Enrique Reales; Pérez, Carol Patricia Figueroa; Gómez, Jairo Antonio Guevara (Journal of Posthumanism, 2024)
This article is part of a broader study that has as its main intention to determine what types of violence and exclusions are carried out at the Popular University of Cesar, this study has been carried out since 2022 and to date the first conclusions have been obtained. The authors, professors from different faculties of the university, using quantitative research under a descriptive and cross-sectional perspective through the use of surveys, revealed revealing perceptions about discrimination, violence and exclusion in the academic environment. Students, predominantly young adults between the ages of 18 and 24, have expressed that a lack of socio-emotional skills contributes significantly to exclusion and discrimination.